Arguments to the norm in the discourses of V. V. Putin and D. A. Medvedev: Аргументы к норме в дискурсах В. В. Путина и Д. А. Медведева - Dudek-Waligóra, Dudek-Waligóra (Przegląd Wschodnioeuropejski, 2019)
The article presents arguments to the norm in the discourse of V. V. Putin and D. A. Medvedev. Such arguments appeal to the norm, custom, rule as the criterion of the correctness of judgments. The material for research is served by the official speeches made by Russian political leaders, and which cover the period from 2014 to 2016. The author gives the examples of examined arguments and analyzes norms, standards to which Russian politicians are referring. The article also stresses the functions of arguments to the norm in the political texts of V. V. Putin and D. A. Medvedev. The paper shows that both Russian leaders appeal to international law, Russian legislation, public practice and economic rules as to the norms justifying the thesis. Therefore Putin and Medvedev build the image of politicians who pay attention to principles of public life. The main purpose of these arguments is to function as unarguable facts and persuade voters to accept decisions discussed.